In search of opportunities for development of microinsurance by drawing on the experience of previous generations - Sułkowska, Wanda (Ekonomia i Prawo. Economics and Law, 2021)
Motivation: Notwithstanding the 30 years of the market economy, the Polish insurance market still reveals an exceptionally low level of penetration rates and insurance density. Attempts should be made to reduce the protection gap by introducing and popularising microinsurance products. Aim: The research aims to establish whether there exists a need for microinsurance products in Poland and whether there are conditions for its development, which groups it should target and what methods and institutions can reduce the protection gap. Results: Data analysis demonstrated that in Poland the lowest use of insurance coverage to manage risk occurs in the lowest income households, comprising groups of people with relatively low education: disability pensioners, farmers and workers. This results in lack of or limited access to insurance. Looking for a way to counteract this phenomenon, I suggest introducing and popularising microinsurance products targeting towards the above-mentioned groups. However, the use of remote microinsurance distribution channels may prove highly ineffective. Considering the above and the lack of trust in entities operating in the insurance market, it is recommended to create a legal environment enabling the inclusion of institutions and organisations acceptable to and enjoying the trust of these circles in processes involving marketing, distribution and, partially, the servicing of microinsurance. These players should consist of civic organisations, such as volunteer fire brigades, rural housewives’ clubs, activist organisations from religious communities, as well as those set up for mutual protection, e.g., relief and loan funds and savings and loan funds. A separate group targeted by microinsurance should consist of people who are young, open to new trends and interested in obtaining insurance coverage for a limited time, e.g., for the short period when they use a means of personal transport or other rented equipment, for which coverage can be obtained and paid for quickly and without undue formalities.